Postoperative evaluation of visual and cognitive functions following cataract surgery in patients with age-related cataracts: a prospective longitudinal study - Zhao, Chenzhu; Li, Xuan; Deng, Bolin; Shui, Bingyue; Zhou, Lin; Wu, Zhengzheng (Frontiers in Neuroscience, 2025)
IntroductionCataracts are associated with a decline in both cognitive and visual functions. This study examines postoperative changes in cognitive and visual functions in patients with age-related cataracts, focusing on the differential effects of unilateral and bilateral cataract surgeries on these functions. Additionally, the study evaluates changes in cognitive function following cataract surgery in individuals with mild cognitive impairment (MCI).MethodsA cohort of patients (n = 35, 59 eyes) aged 60 years and older (69.9 ± 7.0 years) with age-related cataracts who underwent unilateral or bilateral cataract surgery between May and June 2024 was selected. Cognitive and visual functions were evaluated preoperatively and at 1 week, 1 month, and 3 months postoperatively. Cognitive function was evaluated using the Montreal Cognitive Assessment (MoCA). Visual function was assessed using a binocular visual function testing system based on virtual reality (VR) technology, which evaluated low spatial frequency suppression, simultaneous vision, stereopsis, and perceptual eye position under 3D viewing conditions without glasses. Based on preoperative MoCA scores, patients were classified into cognitively normal and mild cognitive impairment (MCI) groups.ResultsPatients with age-related cataracts demonstrated significant improvements in both cognitive and visual functions at 1 week, 1 month, and 3 months postoperatively, compared to preoperative assessments (p < 0.05). Specifically, both the bilateral surgery group and the MCI group exhibited substantial improvements in cognitive function at these time points (p < 0.05). Additionally, the bilateral surgery group outperformed the unilateral surgery group in cognitive function throughout the follow-up period (p < 0.05). In terms of visual function, the bilateral surgery group showed significant improvements in low spatial frequency suppression, simultaneous vision, and stereopsis at 1 week, 1 month, and 3 months postoperatively, compared to preoperative measurements (p < 0.05).ConclusionBoth cognitive and visual functions significantly improved after cataract surgery. Bilateral cataract surgery is more effective in increasing the cognitive functions than unilateral surgery. Additionally, cataract surgery plays a critical role in facilitating cognitive recovery in patients with mild cognitive impairment (MCI).